Non-psychotic denial of pregnancy: A psychoanalytical comprehension - Gonçalves, Thomás; Macedo, Monica; Conz, Jaqueline (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
This paper explores the phenomenon of non-psychotic denial of pregnancy, a situation in which the woman is unaware that she is pregnant for up to five months or more, or until labor. This phenomenon is explored through three different psychoanalytical concepts: disallow, unthinkable pregnancy and indifference experience. The disallow defense mechanism, in cases of denial of pregnancy, is considered as an explanation why women do not link their bodily changes with a possible pregnancy. It appears that women cannot link the sexual act to pregnancy if they have suffered because of a traumatic situation. These situations are explained in the concept of unthinkable experience. In this paper, indifference experience is related to borderline patients, a possible psychopathological structure for women who do not know they are pregnant.